DAS seismic monitoring of the shallow CO2 controlled-release experiment at the South West Hub In-Situ Laboratory. Issue 1 (1st December 2019) - Tertyshnikov, K.; Pevzner, R.; Freifeld, B.; Ricard, L.; Avijegon, A.
Summary: Carbon Capture and Storage (CCS) remains one of the most viable short-term options for halting the increase in atmospheric concentration of greenhouse gases. Assurance of storage safety is an essential part of the process required to maintain a community operations licence. Ability to understand the migration behaviour of CO2 in the shallow subsurface and faults is essential for leakage detection and mitigation. Here we present the results of the successful detection and monitoring of a shallow injection of extremely a small quantity of carbon dioxide into a fault zone using a borehole seismic technique with fibre optic sensors. The experiment was conducted at the South West Hub In-Situ Laboratory in Western Australia.